Hubungan Media Pembelajaran Daring dengan Motivasi Belajar Peserta Didik Paket C PKBM Budi Utama Surabaya - Ichda Chusnia Turrizki; Sjafiatul Mardliyah (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2023)
PKBM Budi Utama is a non-formal education with an equality program package A, package B, and package C. New learning habits using the internet that were carried out after the COVID-19 pandemic depended heavily on learning media. Learning motivation of students has a relationship with the learning process carried out between educators and students. Purpose of this study was to determine the relationship between online learning media and the learning motivation of package C students at PKBM Budi Utama Surabaya. The research approach is quantitative and correlational research type. The test results show a correlation coefficient of 0.999, which is a very strong relationship between the x variable and the y variable. The significance test uses the Spearman rank with the result of a p-value of 0.000 which is then compared to (0.000 <0.05) from the above test H0 is rejected, Ha is accepted. The conclusion is a relationship between online learning media and the learning motivation of package C PKBM Budi Utama Surabaya students.